Cassia occidentalis Potentiates wound Healing Process in Type-2 Diabetic Rats - Pawar, Rajesh Singh; Mandloi, Avinash Singh; Patil, Umesh Kumar; Kumar, Shweta (Indian Journal of Natural Products, 2022)
Introduction: This work is focus on a cost-effective herbal hydrogel formulation comprising of extract, from the leaves of Cassia occidentalis L. (Caesalpiniaceae). The formulation is highly effective for delayed wound healing due to diabetes. Background: Cassia occidentalis (CO) is extensively used in folklore medicine system. It is a common weed scattered from foothills of Himalayas to West Bengal, South India, Burma and Srilanka. Objectives: The study aimed to explore the role of Cassia occidentalis (leaf) for wound healing potential in diabetic rats using the excision wound model. Materials and Methods: The characterization of the phytoconstituents and bioavailability profiles of methanolic extract of CO (MCO) were investigated using High-Performance Liquid Chromatography-Photodiode Array Detector analysis. Insulin resistance was induced in rats by feeding them a diet rich in fructose and hyperglycemia was induced by injecting streptozotocin (STZ) at a dose of 40 mg/kg body weight (bw), intraperitoneally (ip). After confirmation of diabetes fasting blood glucose level, the wound was induced. Excision wound healing activity was examined on Wistar rats. Results: The hydrogel of MCO (5 and 10%) reduced significantly wound size. Significant mean epithelialization period, higher hydroxyproline content and tensile strength were revealed at the concentrations of MCO hydrogel of 5 and 10% compared to the diabetic wound control group. Conclusion: These results provide promising baseline information for the wound healing potential of MCO in type-2 diabetes treatment.
Keywords: Cassia occidentalis; Hyperglycemia; Hydroxyproline; Hydrogel; Biochemical; parameters